Utilizing perspectives from HIV-infected women, male partners and healthcare providers to design family planning mobile health messaging in Kenya: a qualitative study - Lewis, Karren Dorothy (My University, 2017)
Short messaging systems (SMS) present an opportunity to expand the reach of clinical care and improve reproductive health outcomes. SMS could reduce unmet need for family planning (FP) through education, support and demand generation. However the best approach for using SMS to increase FP has not been demonstrated and content of messaging may be critical. We conducted focus group discussions with HIV-infected women, in-depth interviews with male partners of HIV positive women, and with health care workers at one urban and two rural clinics in Kenya to design SMS message content for a larger trial. Many women and men felt SMS could be used as a tool to discuss FP with their partners, and help decrease misconceptions about FP by repeat exposure to validated information. Women felt that SMS enabled them to be more comfortable discussing sensitive topics and lessened power differentials with partners and HCWs compared to in-clinic discussions of FP. However, many women expressed concerns about FP SMS given covert FP use and potential for partner disapproval. This was often found among women who had not disclosed their HIV status and had similar misgivings about overt HIV messages. Providers felt SMS was an important tool for appointment reminders, tracking patients and clinical triage. However, SMS was not viewed as able to replace clinical visits, especially around FP counseling and options. Our findings suggest that SMS messaging could be a powerful tool to facilitate communication within partner and potentially facilitate provider discussion around FP.
Thesis (Master's)--University of Washington, 2017-06
Keywords: family planning; HIV; mHealth; Public health; Global Health